Od kwantu energii do mózgu tworzącego świadomość - Jarosław Grybko (Colloquia Theologica Ottoniana, 2015)
The evolution of the universe from the first particles to human – being conscious indicates the possibility of material transduction molecules. Derived from the Big Bang, particles are suitably configured generate new nature effects: consciousness, mind and self. The source of this process is the human brain. Neurobiological substrate of these phenomena are caused due to patterns of synaptic neuronal communication. You can specify the structure, whose activity marks the effects of mental phenomena, but they can not identify with them. We do not know the cause transduction capacity of the human brain. From an evolutionary point of view of the matter they are constantly being discovered. A man and his brain are the key to this mystery.